Analisis Kualitas Pelayanan Terhadap Kepuasan Pelanggan : Studi Kasus Pelayanan Internet Banking (Klik BCA) Pada PT. BCA, Tbk. Cabang Merdeka - Supariyani, Emmy; Tony, Tony (Sekolah Tinggi Ilmu Ekonomi Kesatuan, 2008)
The purpose of this research is to learn of how far satisfaction level perceived by customers to internet banking sevice and the influence of internet banking service to customers satisfaction. The analysis outcome of customers satisfaction to internet banking system service (click BCA) shows that customers have gotten satisfaction from internet banking service by PT BCA Tbk. Regression analysis result of quality influence of internet banking service to customers satisfaction is function-y = 51,598 + 0,423 (x). This result means that if variable point (x) of internet banking service quality = 1, customers satisfaction nowadays = 52,021. This equation functions to predict if variable (x) of service quality increases, customers satisfaction will increase as well. From counting result of correlation coefficient, it can be found out that r = 0,436. It means that there is moderate and significant correlation between the quality of internet banking service and customers satisfaction. The outcome of determinant coefficient shows that the quality of internet banking service has contribution runs at 19,009% in creating customers satisfaction and the rest runs at 83,991% is influenced by other service quality such as m-banking service, BCA ATM, credit facility, BCA cash, export-import facility, foreign currency facility, and guarantee bank. Keywords: Service quality; Customers satisfaction.